Superstition & science mystics, sceptics, truth-seekers and charlatans - Wilson, Derek (Robinson, 2019)
Between the Renaissance and the Enlightenment, Europe changed out of all recognition as thinkers were driven by a passionate quest for knowledge. Alongside monumental scientific discoveries such as how blood moves around the body, that the earth revolves around the sun and why objects fall, traditional faith flourished and there was an almost universal belief in horoscopes and magic.